2005
DOI: 10.1111/j.1463-1318.2005.00767.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of circumferential margin involvement between restorative and nonrestorative resections for rectal cancer

Abstract: Objective To study circumferential margin involvement (CMI) in patients undergoing restorative, compared with nonrestorative, surgery for rectal cancer.Data source Descriptive multicentre study, using routinely collected clinical data from the Association of Coloproctology of Great Britain and Ireland (ACPGBI) Bowel Cancer Audit database. The study encompassed 1403 newly diagnosed patients with rectal cancer undergoing either restorative (anterior resection (AR)), or nonrestorative (abdominoperineal excision o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 21 publications
8
74
3
1
Order By: Relevance
“…The current practice of TME facilitates radical clearance not only of the primary tumour but also all mesorectal tissues enveloped in the visceral pelvic fascia. This technique has been clearly demonstrated to improve local recurrence rate and 5 year survival [22][23][24]. However, recent studies of more than 1000 patients even with optimal surgical technique have reported CRM involvement rates of between 6.7% and 7.5% after anterior resection and between 16.7% and 17.6% for low rectal cancers requiring abdominoperineal excision (APER) [8,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current practice of TME facilitates radical clearance not only of the primary tumour but also all mesorectal tissues enveloped in the visceral pelvic fascia. This technique has been clearly demonstrated to improve local recurrence rate and 5 year survival [22][23][24]. However, recent studies of more than 1000 patients even with optimal surgical technique have reported CRM involvement rates of between 6.7% and 7.5% after anterior resection and between 16.7% and 17.6% for low rectal cancers requiring abdominoperineal excision (APER) [8,23].…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been clearly demonstrated to improve local recurrence rate and 5 year survival [22][23][24]. However, recent studies of more than 1000 patients even with optimal surgical technique have reported CRM involvement rates of between 6.7% and 7.5% after anterior resection and between 16.7% and 17.6% for low rectal cancers requiring abdominoperineal excision (APER) [8,23]. The evidence base for radiotherapy in operable rectal cancer is discussed at length by Craven and Sebag-Montefiore [25].…”
Section: Discussionmentioning
confidence: 99%
“…De Novo: [709,754,755] Konsens Hintergrund Bei der Rektum-Exstirpation ist klassisch die Rate an Präpara-ten mit unzureichenden lateralen Sicherheitsabständen erhöht [754]. Die onkologischen Ergebnisse sind gegenüber Sphinktererhaltenden Eingriffen bei vergleichbaren Tumorstadien schlechter [755].…”
Section: Level Of Evidence 3bunclassified
“…This risk entering the tumour, which may lead to an involved circumferential resection margin (CRM) and greatly increases the risk of local recurrence [5]. Large national audits have demonstrated that the CRM involvement rates are far higher after APE than after anterior resection [6]. As a consequence of the high local failure rates in patients undergoing APE, the technique of extralevator abdominoperineal excision (ELAPE) has been promulgated by Holm.…”
Section: Introductionmentioning
confidence: 99%